Anatomy of avian rictal bristles in Caprimulgiformes reveals reduced tactile function in open‐habitat, partially diurnal foraging species. Issue 2 (23rd March 2020) - Delaunay, Mariane G.; Larsen, Carl; Lloyd, Huw; Sullivan, Matthew; Grant, Robyn A.
Abstract: Avian rictal bristles are present in many species of birds, especially in nocturnal species. Rictal bristles occur along the upper beak and are morphologically similar to mammalian whiskers. Mammalian whiskers are important tactile sensors, guiding locomotion, foraging and social interactions, and have a well‐characterised anatomy. However, it is not yet known whether avian rictal bristles have a sensory function, and their morphology, anatomy and function have also not been described in many species. Our study compares bristle morphology, follicle anatomy and their association with foraging traits, across 12 Caprimulgiform species. Rictal bristle morphology and follicle anatomy were diverse across the 12 species. Nine of the 12 species had mechanoreceptors around their bristle follicles; however, there was large variation in their musculature, mechanoreceptor numbers and bristle morphology. Overall, species with short, thin, branching bristles that lacked mechanoreceptors tended to forage pre‐dusk in open habitats, whereas species with mechanoreceptors around their bristle follicle tended to forage at night and in more closed habitats. We suggest that rictal bristles are likely to be tactile in many species and may aid in navigation, foraging and collision avoidance; however, identifying rictal bristle function is challenging and demands further investigation in many species. Abstract : Rictal bristle morphology and follicle anatomy are diverse across certain Caprimulgiform species. Species with short, thin, branching bristles that lack mechanoreceptors tend to forage pre‐dusk in open habitats, whereas species with longer rictal bristles and mechanoreceptors around their bristle follicle tend to forage at night and in more closed habitats.